Market presence, contestability, and the terms-of-trade effects of regional integration - Schiff, Maurice W., 1950- 1950- (Policy research working paper, 2001)
How firms react to a given shock may depend on the degree to which rivals are present and on whether potentially viable entrants to that market exist. A preferred supplier market presence and threat of entry lessen a nonmember country's price reaction to most-favored-nation trade liberalization and increase its price reaction to preferential trade liberalization